2015
DOI: 10.1002/jrs.4760
|View full text |Cite
|
Sign up to set email alerts
|

Large scale synthesis of pinhole‐free shell‐isolated nanoparticles (SHINs) using improved atomic layer deposition (ALD) method for practical applications

Abstract: Shell-isolated nanoparticle-enhanced Raman spectroscopy (SHINERS) as a new member of Raman technique garnered great attention among scientific community. In this work, we used an improved experimental setup to float the bare silver nanoparticles in air with the help of extraneous airflow, and used atomic layer deposition (ALD) method to coat ultra-thin inert shell without pinholes. Under optimal conditions, we successfully prepared three kinds of SHINERS NPs (Ag@Al 2 O 3 , Ag@SiO 2 and Ag@TiO 2 ) in large quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Besides the chemical method used to prepare shell‐coated metal nanoparticles, atomic layer deposition (ALD) is also an easy route to control the thickness of the oxide shell to the nanoscale. Zhang et al have reported modified ALD to encase bare silver with ultrathin shell materials . In the experimental setup, Ag nanoparticles considerably floated in the chamber on account of the gas flow, which permitted the uniform deposition of silica over metal nanoparticles.…”
Section: Synthesis Of Various Shell‐isolated Nanoparticlesmentioning
confidence: 99%
“…Besides the chemical method used to prepare shell‐coated metal nanoparticles, atomic layer deposition (ALD) is also an easy route to control the thickness of the oxide shell to the nanoscale. Zhang et al have reported modified ALD to encase bare silver with ultrathin shell materials . In the experimental setup, Ag nanoparticles considerably floated in the chamber on account of the gas flow, which permitted the uniform deposition of silica over metal nanoparticles.…”
Section: Synthesis Of Various Shell‐isolated Nanoparticlesmentioning
confidence: 99%
“…In our case, the suitable diameter of gold cores is 55 nm [ 121 ] for SHINERS measurements, and bigger diameter gold NPs, such as 120 nm, can be synthesized for enormous enhancements ( Figure 6 A,B). [ 120,128,129 ] Here, we describe the detailed experimental procedure of SHINs using 55 nm Au@SiO 2 as an example. [ 15,120,[122][123][124][125] The SPR property of nanoparticles will be affected by its shape and size.…”
Section: Progress Reportmentioning
confidence: 99%
“…Finally, the sample was subjected to Raman measurements. [ 129 ] Copyright 2015, Wiley. Optical Mater.…”
Section: Characterization Of Shinsmentioning
confidence: 99%
“…studied the size‐dependent evolution of phonon confinement in colloidal Si nanoparticles using SERS. By introducing a variable confinement factor, α, into a well‐known phenomenological phonon confinement model (PCM) developed by Richter et al ., acceptable fits were achieved to downshifted and asymmetrically broadened Raman spectra of Si NPs with different diameters …”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%